Influence of long-term fertilization on soil aggregates stability and organic carbon occurrence characteristics in karst yellow soil of Southwest China - Liu, Yanling; Zhang, Meng; Xiong, Han; Li, Yu; Zhang, Yarong; Huang, Xingcheng; Yang, Yehua; Zhu, Huaqing; Jiang, Taiming (Frontiers in Plant Science, 2023)
Soil organic carbon (SOC) and soil agglomerate stability have always been a hot topic of current research. However, the effects of long-term different fertilization on yellow soil aggregate composition and organic carbon fugacity characteristics in the karst region of southwest China are still unclear. In this study, soil samples from a 25-year long-term location test were collected, and soil aggregate composition was determined using the dry sieve method and wet sieve method, and soil aggregate stability, aggregate carbon sequestration characteristics and carbon pool management index were analyzed. The results showed that both soil mechanical-stability agglomerates (MSAs) and water-stability agglomerates (WSAs) were dominated by >5 mm agglomerates, and different fertilizer applications significantly affected the composition of water stability agglomerates. The application of organic fertilizer significantly increased the content of >5 mm agglomerates and the stability of agglomerates, while the application of chemical fertilizer alone significantly increased the content of 2-0.25 mm and <0.25 mm agglomerates and the stability of agglomerates. Meanwhile, the organic carbon and active organic carbon content in soil aggregates increased with the increase of organic fertilizer dosage. The application of organic fertilizer significantly increased the carbon sequestration capacity of organic carbon and active organic carbon in total soil and large agglomerates. In contrast, chemical fertilizer alone significantly increased the carbon preservation capacity of organic carbon and active organic carbon in micro-aggregate. Long-term application of organic fertilizer also significantly increased the contribution of organic carbon in large-aggregate and improved the quality of soil organic carbon pool. In addition, the results of multivariate statistical analysis showed that TOC was the most important physicochemical factor affecting the composition and stability of soil aggregates. In conclusion, the application of organic fertilizer can significantly increase the content of soil large-aggregate and promote the allocation of organic carbon to large-aggregate and improve the soil carbon pool management index, which is an effective measure to improve yellow soil structure and enhance soil carbon sequestration capacity in karst areas.